1972
DOI: 10.1210/endo-90-3-808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACTH on Cholesterol Dynamics in Rat Adrenal Tissue

Abstract: Cholesterol dynamics involving esterification and hydrolysis in rat adrenal tissue divided into the zona fasciculata and reticularis (the decapsulated gland) and the zona glomerulosa (the capsular gland) have been studied. Estimation of esterifying activity was based on the radioactivity of the cholesterol ester formed during incubation with palmitate-l-14 C. The activity of esterase was measured by the radioactivity of fatty acid hydrolyzed from cholesteryl-palmitate-l-14 C during incubation.Both activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0
1

Year Published

1973
1973
1997
1997

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 8 publications
2
11
0
1
Order By: Relevance
“…Shima et al (20) reported that cholesterol dynamics including esterification, hydrolysis and mobilization for steroidogenesis are working more in the decapsulated zone (fasciculata and reticularis) than in the capsular (glomerulosa), which supports our results that the effect of ACTH was mainly seen in the zonae fasciculata and reticularis. Boyd and Trzeciak (3) suggested that the supply of cholesterol to mitochondria from the cholesterol ester pool in the LD could be a rate-limiting factor in the process of steroidogenesis in the adrenals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Shima et al (20) reported that cholesterol dynamics including esterification, hydrolysis and mobilization for steroidogenesis are working more in the decapsulated zone (fasciculata and reticularis) than in the capsular (glomerulosa), which supports our results that the effect of ACTH was mainly seen in the zonae fasciculata and reticularis. Boyd and Trzeciak (3) suggested that the supply of cholesterol to mitochondria from the cholesterol ester pool in the LD could be a rate-limiting factor in the process of steroidogenesis in the adrenals.…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, hypophysectomy has been reported to cause accumulation of cholesterol esters in the LD of the zonae fasciculata and reticularis (13,20,22). The monochromatic CL images of the hypophysectomized rat adrenal cortex clearly showed that CL of 320 nm emitted from the LD of the zonae fasciculata and reticularis cells increased and that of 430 nm significantly decreased.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous experiments on rat adrenal glands (12,17,28) revealed that the adenyl cyclase activities of the capsular and the decapsulated were the same, regardless of great differences in steroidogenic responses to ACTH between the two zones. In the present paper, the activity of CAMP binding and protein kinases stimulated by CAMP was also similar in the capsular and the decapsulated zone.…”
Section: Discussionmentioning
confidence: 93%
“…However very little information on the adrenal cholesteryl esterase is available and no thorough investigation of the enzyme has been reported. A recent report [8] revealed that adrenal cholesteryl esterase activity could be sigrdcantly enhanced by the prior injection of adrenocorticotrophic hormone into rats. There k also evidence that in perfused rat adrenal glands, cholesterol ester hydrolysis is stimulated by adrenocorticotrophic hormone.…”
mentioning
confidence: 99%